a)
$$\begin{align}&\frac{sen^4x}{\cos^4x}-\frac{1}{\cos^4x}=\\ &\\ &\\ &\frac{sen^4x-1}{\cos^4x}=\\ &\\ &\\ &\text{Usamos que } a^2-b^2=(a+b)(a-b)\\ &\text{Siendo }a=sen^2x,\;b=1\\ &\\ &=\frac{(sen^2x+1)(sen^2x-1)}{\cos^4x}\\ &\\ &\\ &= \frac{(sen^2x+1)(-\cos^2x)}{\cos^4x}=\frac{-sen^2x-1}{\cos^2x}\\ &\\ &\text{Y en el lado derecho}\\ &\\ &1-\frac{2}{\cos^2x}=\frac{\cos^2x-2}{\cos^2x}=\\ &\\ &\text{Como }-1 =-sen^2x-\cos^2x\\ &\\ &=\frac{\cos^2x-sen^2x-\cos^2x-1}{\cos^2x}=\\ &\\ &\\ &\frac{-sen^2x-1}{\cos^2x}\end{align}$$
Luego los dos lados son iguales.
b)
$$\begin{align}&\frac{1}{\cos^4t}-\frac{1}{\cos^2t}=\frac{1-\cos^2t}{\cos^4t}=\frac{sen^2t}{\cos^4t}\\ &\\ &\\ &\text{Y en el lado derecho}\\ &\\ &\frac{sen^2t}{\cos^2t}+\frac{sen^4t}{\cos^4t}=\\ &\\ &\\ &\frac{sen^2t·\cos^2t+sen^4t}{\cos^4t}=\\ &\\ &\\ &\frac{sen^2t(\cos^2t+sen^2t)}{\cos^4t}=\frac{sen^2t}{\cos^4t}\end{align}$$
Luego los dos lados son iguales.
Y eso es todo.